What it takes to be a “Good” correctional officer: Occupational fitness and co-worker expectations from the perspective of correctional officer recruits in Canada - Cassiano, Marcella Siqueira (Criminology & criminal justice, 2024)
Selecting individuals who are the right “fit” for correctional work is not an easy task for prison administrators because of the dangerous nature of correctional work and the centrality of prison employees in the prisoner’s rehabilitation process. We analyze fitness for correctional work from the employee’s perspective, complementing the scholarship focused on the employer’s view. We measure occupational fitness in terms of co-worker expectations, analyzing 104 semi-structured interviews conducted with Federal Canadian Correctional Officer recruits in 2018/2019. Recruits in our sample expected a correctional officer to be accountable, reliable, and confident. Understanding the mind-set of new hires provides insights into the correctional officer role and allows employers to align employer-employee expectations, as well as review training and recruitment, which can improve the employee well-being and reduce turnover rates.